Home recording technique training for the pare strings ensemble community - East Java - Anggoro, Raden Roro Maha Kalyana Mitta; Karyawanto, Harpang Yudha; Murbiyantoro, Heri; Dharmawanputra, Budi; Mahendra, Marda Putra (Universitas Ahmad Dahlan, 2023)
College may be a logical institution that has the most assignment of carrying out the Tri Dharma of College, specifically instruction and instructing, research, and community service. Through the assignments it carries out, it is trusted that university educate will gotten to be centers of total human advancement as well as upkeep and advancement of science, innovation and arts in understanding with current and future needs. As with other Art Colleges in Indonesia, the Music Study Program, Faculty of Languages ​​and Arts, Universitas Negeri Surabaya, in arrange to execute the Tri Dharma of College and “One Step Ahead” endeavours, different exercises were carried out which were showed within the frame of